The cost saving method: A proposal of awqaf alternative plan - Anwar Allah Pitchaya; Mohd Najwadi Yusoff Abdul Rahman; Mohamad Isa Abd Jalil; Zubir Azhar; Mohamed Asmy Mohd Thas Thaker (Labuan e-Journal of Muamalat & Society, 2022)
The aim of the paper is to propose an improved food and beverages (F&B) cost estimation to the higher education institution. The method integrates personal observation and interview with the vice-chancellor of a public university in Malaysia. The proposed model, Awqaf Alternative Plan (AAP) is able to address the problem of top management of the university to estimate the actual cost of organizing an event. Besides, AAP model also creates a new platform/option for the students and staffs to donate university fund back their respective university inform of waqf/endowment fund which can be used for the development of the campus. AAP model is relevant to the management of the university to estimate accurate cost which leads to sustainable internal cost management. Besides, the effective management of cost is the main objective which able to promote sustainable cost saving. AAP model is a cost-saving approach which specifically proposed to a higher institution.